2009
DOI: 10.1021/jp9026767
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Dependent Hydrogen Permeability Extended for Metal Membranes Not Obeying the Square-Root Law

Abstract: Hydrogen permeability of metal membranes is generally defined by the square-root law, as the proportional coefficient of permeation flux to the square-root difference of the pressures on both sides of the membrane. However, deviation from the law has been widely reported for palladium, niobium, etc. Although n-th power instead of the square root has often been employed to determine permeability for these membranes, it has no theoretical base. These approaches do not consider concentration dependency of hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…The pressure dependency is the smaller at the lower pressures and the higher temperatures. These characteristics are the same as those for the 50 µm membrane reported previously [6].…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The pressure dependency is the smaller at the lower pressures and the higher temperatures. These characteristics are the same as those for the 50 µm membrane reported previously [6].…”
Section: Resultssupporting
confidence: 85%
“…These definitions are explained in detail in a previous report [6]. Conventional square-root law, power law and extended law in this study are compared in Table 1 On the other hand, the power law can often describe permeation behavior more precisely than the square-root law.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Summary of reported hydrogen permeability values for Ni-based amorphous alloy membranes and selected Pd-based alloys as reference materials equilibrium hydrogen concentration did not obey Sieverts law, however, and was nearly linear with the quarter power determined using Kirchheim theory. Hara et al [39] established a theory of permeability as a function of hydrogen pressure and developed equations for pressure dependent permeability from permeation tests. They also reported that the dissolution of hydrogen did not obey Sieverts' law (i.e., proportional to P 0.5 ).…”
Section: Amorphous Ni-based Membranesmentioning
confidence: 99%
“…To understand these exceptional cases, Hara et al have recently proposed a concept based on the pressure dependent hydrogen permeability. [17][18][19] It is well known that the gradient of hydrogen concentration, dc/dx, is not always the driving force for hydrogen diffusion. Strictly speaking, the hydrogen diffusion is driven by the gradient of the hydrogen chemical potential, dl/dx.…”
Section: Introductionmentioning
confidence: 99%